ULF waves and magnetic field characteristics in the polar cusp observed at Godhavn - Sakurai, Tohru; Tonegawa, Yutaka; Kato, Ken-ichi; Makita, Kazuo; Ejiri, Masaki; Yamagishi, Hisao; Sato, Natsuo (National Institute of Polar Research, 1993)
P(論文) For the intrusion of the solar wind energy into the magnetosphere the polar cusp has been believed to be the most important region in the magnetosphere. By using magnetometer data obtained in November 1989 at Godhavn (Inv. Lat.=76°) in Greenland located in the polar cusp the dayside enhancement of ULF wave activity is studied in relation to both variations of the ground magnetic field and the interplanetary magnetic field. The important results are as follows; 1) Godhavn is found to be one of the appropriate stations for studying magnetic field variations and ULF waves in the polar cusp, i. e., the normal-run magnetograms show negative H component excursion during the daytime, sometimes sporadically and in the other times gradually. The ULF waves enhance their activity closely associated with these negative field variations. These field variations might be considered to occur when the station passes under the westward current flowing in the cusp ionosphere. 2) By comparing the ground magnetic activities with the interplanetary magnetic field the ground magnetic activities occur in association with high frequency fluctuations of the IMF. 3) A comparison of spectral power of the ULF waves at Godhavn (cusp latitude) with those at Syowa (auroral latitude) shows more enhanced magnetic power and more resonance-like oscillation of ULF waves at the auroral latitude. Thus, the cusp might be a source region of magnetic energy penetrating into the magnetosphere, and resonant oscillations of ULF waves are clearly observed at the auroral latitude. departmental bulletin paper